The Dimensions Of The Learning Organization In Omani School From Employees Point Of View - Mahmoud Mohamed Ali; Kirembwe Rashid Abdulhamed; Said Salim Aljamoudi (International Journal of Scientific & Technology Research, 2024)
Abstract: This research is aimed to study the existence of the dimensions of the learning organization in basic education schools in the Sultanate of Oman from its employees' point of view. Also, this study aims to identify the differences in the estimates of workers in basic education schools to the presence of learning organization requirements attributable to any of the variables of gender, and qualification. A theoretical framework of learning organizations developed by the researcher is used in this research. The questionnaire was used as a tool to get to know the reality of the existence of the requirements of the learning organization on a sample consisting of (1098) of the workers in basic education schools. The research concludedthat to become a learning organization, basic education schools in the Sultanate of Oman needs to promote allthedimensions of the learning organization.